Mitochondrial DNA Variation in Peruvian Honey Bee (Apis mellifera L.) Populations Using the tRNAleu-cox2 Intergenic Region - Chávez Galarza, Julio César (2021)
Mitochondrial DNA variations of Peruvian honey bee populations were surveyed by using the tRNAleu-cox2 intergenic region. Only two studies have characterized these populations, indicating the presence of Africanized honey bee colonies in different regions of Peru and varied levels of Africanization, but the current status of its genetic diversity is unknown. A total of 512 honey bee colonies were sampled from three regions to characterize them. Our results revealed the presence of European and African haplotypes: the African haplotypes identified belong to sub-lineage AI (13) and sub-lineage AIII (03), and the European haplotypes to lineages C (06) and M (02). Of 24 haplotypes identified, 15 new sequences are reported here (11 sub-lineage AI, 2 sub-lineage AIII, and 2 lineage M). Peruvian honey bee populations presented a higher proportion from African than European haplotypes. High proportions of African haplotype were reported for Piura and Junín, unlike Lima, which showed more European haplotypes from lineage C. Few colonies belonging to lineage M would represent accidental purchase or traces of the introduction into Peru in the 19th century.